A Comparative Study on the Effect of Multiple Inheritance Mechanism in C++, C#, Java, Python and PHP on Complexity and Reusability of Code - Geetanjali Dogra, Jagjit Kaur, Reecha Sood, Mandeep kaur, Upinderpal Singh (International Journal of Advanced Science and Technology, 2019)
Multiple inheritance is one of the most important aspects of OOP programming language in which a child class can inherit features or attributes from more than one base class or parent class. But in single inheritance, one child class only inherits from exactly one base class. The “DIAMOND PROBLEM” and other ambiguities has led the Multiple inheritance to be a very sensitive topic and issue for many years, the scenario with this inheritance is very complex and causing the real world programs to have increased complexities..In this paper we have studied several types of Inheritance, with main focus on multiple inheritance with their related issues and how it is implemented in different object-oriented programming languages. Keywords: Biometrics, Iris Recognition, Periocular Recognition, Covariate